The Impact of Entrepreneurial Strategies on Organizational Performance Quality: The Role of Innovation as a Mediating Variable - Al-Kharabsheh, Sami Awwad Ismail (International Review of Management and Marketing, 2026)
Entrepreneurial strategies become essential tools for assessing an organization's success as it navigates the competitive and changing business environment. The several facets of ES are the focus of this research, with innovation serving as a mediator. The top ten manufacturing SMEs in Amman, Jordan, provided data to confirm the influence of the ES dimensions (risk-taking, proactiveness, autonomy, and competitive aggression) on the OPQ. The data gathered from 298 questionnaires were analyzed using the PLS-SEM technique. These SMEs may think about focusing on innovation, risk-taking moderation, proactiveness, competitive aggression, and autonomy to increase their competitiveness and adaptability in the fast-paced dynamic environment. This, in turn, enables companies to capitalize on opportunities, launch new products, and enter new markets, all of which work to improve financial performance and drive sustainable growth. They need to establish entrepreneurial strategies for SMEs to persevere in the current business environment